2018
DOI: 10.3390/s18124489
|View full text |Cite
|
Sign up to set email alerts
|

A Tunable Plasmonic Refractive Index Sensor with Nanoring-Strip Graphene Arrays

Abstract: In the present study, we design a tunable plasmonic refractive index sensor with nanoring-strip graphene arrays. The calculations prove that the nanoring-strip have two transmission dips. By changing the strip length L of the present structure, we find that the nanoring-strip graphene arrays have a wide range of resonances (resonance wavelength increases from 17.73 μm to 28.15 μm). When changing the sensing medium refractive index nmed, the sensitivity of mode A and B can reach 2.97 μm/RIU and 5.20 μm/RIU. By … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…When θ increased, the wavelength of the three absorption peaks almost remained unchanged, and the absorption intensity changed inconspicuously, which indicated the structure was angle insensitive. Because the guided mode resonance was insensitive to the incident angle [34,[47][48][49][50], this provides useful application value in integrated optoelectronic devices. Therefore, we proved that the designed structure could simultaneously achieve critical coupling of multiple resonances, which is the main technical index of multispectral optical detection.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When θ increased, the wavelength of the three absorption peaks almost remained unchanged, and the absorption intensity changed inconspicuously, which indicated the structure was angle insensitive. Because the guided mode resonance was insensitive to the incident angle [34,[47][48][49][50], this provides useful application value in integrated optoelectronic devices. Therefore, we proved that the designed structure could simultaneously achieve critical coupling of multiple resonances, which is the main technical index of multispectral optical detection.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…For instance, a polarization-dependent graphene absorber with a one-dimensional, sub-wavelength dielectric grating has been theoretically proved to be capable of attaining perfect absorption [33]. It has been confirmed that a sub-wavelength structure based on graphene, in TE (the direction of electric field is parallel to y) polarization mode, displays a peak absorption over 99% [34] at a wavelength of about 1500 nm, which explains that a light source with a polarization-independent absorption structure is preferential under normal incident conditions with the purpose of satisfying the application requirements. Piper and Fan demonstrated single-layer graphene with a two-dimensional photonic crystal plate having a high refractive index exhibits perfect absorption in the near-infrared band [35], where the coupled mode theory (CMT) expounds the critical coupling phenomenon [36].…”
Section: Introductionmentioning
confidence: 98%
“…The optical RI sensing is one of the most suitable techniques for the applications mentioned above because the sensors do not require the electrical wiring. Many kinds type of RI optical sensing devices have been developed so far using optical resonances in metal surfaces [ 1 , 8 , 9 , 10 , 11 ], nano particles [ 2 , 3 , 12 , 13 , 14 ], nanorings [ 15 , 16 , 17 ], waveguides [ 18 , 19 , 20 , 21 , 22 ], gratings [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], photonic crystals [ 31 , 32 , 33 , 34 ], and microstructured optical fibers [ 35 , 36 , 37 ]. The systems of RI sensing based on surface plasmon resonance (SPR) have been widely used and been commercialized.…”
Section: Introductionmentioning
confidence: 99%
“…Whether through the development of terahertz technology [1,2,3,4] or the development of perfect absorbers [5,6,7], the emergence of metamaterials has undoubtedly played a role in promoting them. Although terahertz technology has made rapid progress in light sources and detectors [8,9,10,11], it still needs further exploration and research compared with the mature infrared and microwave bands. However, if we want to continue to develop terahertz (THz) technology, we need to solve a difficult problem: finding a kind of material that can strongly respond to the terahertz band.…”
Section: Introductionmentioning
confidence: 99%